MeCP2 regulates ethanol sensitivity and intake. (28th February 2013) - Repunte‐Canonigo, Vez; Chen, Jihuan; Lefebvre, Celine; Kawamura, Tomoya; Kreifeldt, Max; Basson, Oan; Roberts, Amanda J.; Sanna, Pietro Paolo
Abstract We have investigated the expression of chromatin‐regulating genes in the prefrontal cortex and in the shell subdivision of the nucleus accumbens during protracted withdrawal in mice with increased ethanol drinking after chronic intermittent ethanol (CIE) vapor exposure and in mice with a history of non‐dependent drinking. We observed that the methyl‐CpG binding protein 2 (MeCP2) was one of the few chromatin‐regulating genes to be differentially regulated by a history of dependence. As MeCP2 has the potential of acting as a broad gene regulator, we investigated sensitivity to ethanol and ethanol drinking in MeCP2308/Y mice, which harbor a truncated MeCP2 allele but have a milder phenotype than MeCP2 null mice. We observed that MeCP2308/Y mice were more sensitive to ethanol's stimulatory and sedative effects than wild‐type (WT) mice, drank less ethanol in a limited access 2 bottle choice paradigm and did not show increased drinking after induction of dependence with exposure to CIE vapors. Alcohol metabolism did not differ in MeCP2308/Y and WT mice. Additionally, MeCP2308/Y mice did not differ from WT mice in ethanol preference in a 24‐hour paradigm nor in their intake of graded solutions of saccharin or quinine, suggesting that the MeCP2308/Y mutation did not alter taste function. Lastly, using the Gene Set Enrichment Analysis algorithm, we found a significant overlap in the genes regulated by alcohol and by MeCP2. Together, these results suggest that MeCP2 contributes to the regulation of ethanol sensitivity and drinking.